Blood volume fraction imaging of the human lung using intravoxel incoherent motion - Carinci, Flavio; Triphan, Simon M. F. (Journal of magnetic resonance imaging, 2015)
Purpose To present a technique for non-contrast-enhanced in vivo imaging of the blood volume fraction of the human lung. The technique is based on the intravoxel incoherent motion (IVIM) approach. However, a substantial novelty is introduced here: the need for external diffusion sensitizing gradients is eliminated by exploiting the internal magnetic field gradients typical of the lung tissue, due to magnetic susceptibility differences at air/tissue interfaces. Materials and Methods A single shot turbo spin-echo sequence with stimulated-echo preparation and electrocardiograph synchronization was used for acquisition. Two images were acquired in a single breath-hold of 10 seconds duration: one reference image and one blood-suppressed image. The blood volume fraction was quantified using a two-compartment signal decay model, as given by the IVIM theory. Experiments were performed at 1.5T in eight healthy volunteers. Results Values of the blood volume fraction obtained within the lung parenchyma (36 ± 16%) are in good agreement with previous reports, obtained using contrast-enhanced magnetic resonance angiography (33%), and show relatively good reproducibility. Conclusion The presented technique offers a robust way to quantify the blood volume fraction of the human lung parenchyma without using contrast agents. Image acquisition can be accomplished in a single breath-hold and could be suitable for clinical applications on patients with lung diseases.
Gesehen am 29.06.2017